2019
DOI: 10.1039/c9ta00272c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of A-site cations on the open-circuit voltage of efficient perovskite solar cells: a case of rubidium and guanidinium additives

Abstract: The effect of rubidium and guanidinium additives on the morphological, optoelectronic and photovoltaic properties of the state-of-the-art triple A-cation based PSCs is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 53 publications
0
48
1
Order By: Relevance
“…In our previous reports on GUA x MA 1Àx PbI 3 PSCs, we observed a complex impedance peak between 10 5 and 10 6 Hz and the corresponding time constant depicts the recombination kinetics in the cell, which is significantly suppressed upon GUA incorporation. 43,48 However, such high-frequency response is not observed in the present study. In turn, we observed that with incorporation of a small amount of the GUA cation in the MAPbI 3 crystal structure, the rate of change in the apparent time constant is significantly suppressed with a change in temperature.…”
Section: Resultscontrasting
confidence: 87%
“…In our previous reports on GUA x MA 1Àx PbI 3 PSCs, we observed a complex impedance peak between 10 5 and 10 6 Hz and the corresponding time constant depicts the recombination kinetics in the cell, which is significantly suppressed upon GUA incorporation. 43,48 However, such high-frequency response is not observed in the present study. In turn, we observed that with incorporation of a small amount of the GUA cation in the MAPbI 3 crystal structure, the rate of change in the apparent time constant is significantly suppressed with a change in temperature.…”
Section: Resultscontrasting
confidence: 87%
“…This result indicates that the GUA-based perovskite has a smoother contact than the reference sample with the HTL, suggesting better charge transfer at this interface with possibly lower recombination. 37,38…”
Section: Resultsmentioning
confidence: 99%
“…[16] Besides, applying additives can also reduce the defects by regulating the crystallization kinetics process or passivate the defects effectively. [17][18][19] And the common additives are the polymers or small organic molecules with hybrid atoms, such as sulfur (S), oxygen (O), or nitrogen (N) atoms. [17][18][19] The lone pair electrons of hybrid atoms make it possible to chelate with Pb atoms to produce intermediate complex, which is conducive to reduce the defects by regulating the crystallization rate.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] And the common additives are the polymers or small organic molecules with hybrid atoms, such as sulfur (S), oxygen (O), or nitrogen (N) atoms. [17][18][19] The lone pair electrons of hybrid atoms make it possible to chelate with Pb atoms to produce intermediate complex, which is conducive to reduce the defects by regulating the crystallization rate. Therefore, the introduction of additives can reduce the recombination and enhance the comprehensive device performances further.…”
Section: Introductionmentioning
confidence: 99%